Microbiota stimulation generates LCMV-specific memory CD8+ T cells in SPF mice and determines their TCR repertoire during LCMV infection. (August 2020) - Gonçalves, Pedro; El Daker, Sary; Vasseur, Florence; Serafini, Nicolas; Lim, Annick; Azogui, Orly; Decaluwe, Helene; Guy-Grand, Delphine; Freitas, Antonio A.; Di Santo, James P.; Rocha, Benedita
Graphical abstract: Highlights: A major fraction of CD44 hi CD8 + T cells in SPF mice is generated by microbiota stimulation. CD44 hi GP33 + CD8 + T cells express particular TCRβ chains and have an innate like phenotype. These cells proliferate rapidly and dominate the response to primary LCMV infection. Microbiota plays a fundamental role in the LCMV infection, determining the TCR repertoire. Abstract: Both mouse and human harbour memory phenotype CD8 + T cells specific for antigens in hosts that have not been previously exposed to these antigens. The origin and the nature of the stimuli responsible for generation of CD44 hi CD8 + T cells in specific pathogen-free (SPF) mice remain controversial. It is known that microbiota plays a crucial role in the prevention and resolution of systemic infections by influencing myelopoiesis, regulating dendritic cells, inflammasome activation and promoting the production of type I and II interferons. By contrast, here we suggest that microbiota has a direct effect on generation of memory phenotype CD44 hi GP33 + CD8 + T cells. In SPF mice, it generates a novel GP33 + CD44 hi CD8 + T cell sub-population associating the properties of innate and genuine memory cells. These cells are highly enriched in the bone marrow, proliferate rapidly and express immediate effector functions. They dominate the response to LCMV and express particular TCRβ chains. The sequence of these selected TCRβ chains overlaps with that of GP33 + CD8 + T cells directly selected by microbiota in the gut epithelium of SPF mice, demonstrating a common selection mechanism in gut and peripheral CD8 + T cell pool. Therefore microbiota has a direct role in priming T cell immunity in SPF mice and in the selection of TCRβ repertoires during systemic infection. We identify a mechanism that primes T cell immunity in SPF mice and may have a major role in colonization resistance and protection from infection.